UJI FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL DAUN ZODIA (EVODIA SUAVEOLENS) - Ngibad, Khoirul; Lestari, Lilla Puji (Jurnal Ilmiah As-Syifaa, 2019)
Zodia (Evodia suaveolens) plant is commonly used by the community to repel mosquitoes. The plant is native to Papua but has been widely cultivated in Java such as: Batu, Depok, Bogor, Bandung and Surabaya. The aim of this study is to determine the antioxidant activity of zodia leaves methanol extract. In addition, to determine the class of secondary metabolites of the methanol extract of zodia leaves. The extraction process was carried out by maceration method using methanol solvent for 3 days then the filtrate was concentrated using a rotary evaporator. The antioxidant potential of zodia leaves methanol extract was tested using the DPPH method (1,1-Diphenyl-2-picrylhydrazyl) with a UV-Vis spectrophotometer while the determination of secondary metabolite compounds from zodia leaves methanol extract was carried out qualitatively using reagents. The results of the phytochemical test showed that the methanol extract of zodia plant leaves contained group of alkaloid, flavonoids, and tannins compounds while the antioxidant activity test of zodia methanol extract using the DPPH method were shown with an IC50 value of 55,69 ppm while These results indicated that the zodia leaves methanol extracts have strong category of antioxidant activity.